2020
DOI: 10.33552/abeb.2020.03.000572
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Variation of Iliolumbar Artery and its Clinical Significance

Abstract: Our research has shown that the iliolumbar artery with a diameter of 0.23±0.13 cm and a length of 2.33±1.43 cm in most of cases was a branch of the posterior division of the internal iliac artery (in 73.3% of cases). In 16.6%, the ILA took origin from the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The majority of the papers present the origin of the ILA to be from the internal iliac artery or the posterior trunk of the internal iliac artery, with a frequency ranging from 19.0% to 96.3% [4,16,29]. However, a vast number of different origins have also been demonstrated, including origins from the gluteal arteries, the bifurcation point of the internal iliac artery, the sciatic artery, the lateral sacral artery, and the obturator artery, amongst others [4,7,29]. In a study conducted by Al Talalwah et al [29], the most common origin of the ILA was from the posterior trunk of the internal iliac artery (77.9%); however, they reported that the said vessel also originated from the superior gluteal artery (0.7%), inferior gluteal artery (0.3%), and sciatic artery (0.3%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of the papers present the origin of the ILA to be from the internal iliac artery or the posterior trunk of the internal iliac artery, with a frequency ranging from 19.0% to 96.3% [4,16,29]. However, a vast number of different origins have also been demonstrated, including origins from the gluteal arteries, the bifurcation point of the internal iliac artery, the sciatic artery, the lateral sacral artery, and the obturator artery, amongst others [4,7,29]. In a study conducted by Al Talalwah et al [29], the most common origin of the ILA was from the posterior trunk of the internal iliac artery (77.9%); however, they reported that the said vessel also originated from the superior gluteal artery (0.7%), inferior gluteal artery (0.3%), and sciatic artery (0.3%).…”
Section: Discussionmentioning
confidence: 99%
“…Valchkevich and Borel [7] stated that the ILA also forms common trunks with nearby arteries, such as the lateral sacral artery (3.3%) and the obturator artery (3.3%). However, it is important to note that the aforementioned study was conducted on only 15 cadavers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation